2011
DOI: 10.1007/s10646-011-0779-x
|View full text |Cite
|
Sign up to set email alerts
|

Molecular identification of arsenic-resistant estuarine bacteria and characterization of their ars genotype

Abstract: In the present study, 44 arsenic-resistant bacteria were isolated through serial dilutions on agar plate with concentrations ≥0.05 mM of sodium arsenite and ≥10 mM of sodium arsenate from Mandovi and Zuari--estuarine water systems. The ars genotype characterization in 36 bacterial isolates (resistant to 100 mM of sodium arsenate) revealed that only 17 isolates harboured the arsA (ATPase), B (arsenite permease) and C (arsenate reductase) genes on the plasmid DNA. The arsA, B and C genes were individually detect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 50 publications
2
11
1
Order By: Relevance
“…The As(V) and As(III) tolerance levels shown for our three strains contrast with those previously reported for this genus: strains WK6 (Anderson and Cook, 2004), KM05 (Sunita et al, 2012), S17 (Belfiore et al, 2013), PS NCIM 5463 (Sacheti et al, 2014), AS-9 (Pandey and Bhatt, 2015), antarcticum B7 (da Costa et al, 2018), and profundum PT2 (Andreasen et al, 2018). We highlight the ability of SH0S7 strain, isolated from H0 site, to tolerate 20 mM of As(III), one of the highest concentrations reported so far.…”
Section: Discussioncontrasting
confidence: 96%
“…The As(V) and As(III) tolerance levels shown for our three strains contrast with those previously reported for this genus: strains WK6 (Anderson and Cook, 2004), KM05 (Sunita et al, 2012), S17 (Belfiore et al, 2013), PS NCIM 5463 (Sacheti et al, 2014), AS-9 (Pandey and Bhatt, 2015), antarcticum B7 (da Costa et al, 2018), and profundum PT2 (Andreasen et al, 2018). We highlight the ability of SH0S7 strain, isolated from H0 site, to tolerate 20 mM of As(III), one of the highest concentrations reported so far.…”
Section: Discussioncontrasting
confidence: 96%
“…Our results corroborate with the previous study carried out among isolates from municipal wastewater in Italy, where co-occurrence of antibiotic resistance and ars C gene was observed ( Di Cesare et al, 2016 ). Reports from Kaur et al, 2009 , Sunita et al, 2012 also showed the presence of ars C gene among the bacterial isolates from freshwater bodies in India. The association of mobile elements with blaTEM gene was also studied where positive amplification for IntI 81, SulI 63, ISecp1 54, TN3 45, and TN21 63% isolates was achieved.…”
Section: Discussionmentioning
confidence: 90%
“…The amplified products were tested for the possible amalgamations of ESBLs ( blaTEM ) and sil genes besides the determinants mer B, mer P, and mer T genes, that confer the resistance against mercury. Arsenic resistant ( arsC ) gene was also amplified using the primer sequence from previously available literature ( Sunita et al, 2012 ).…”
Section: Materials and Methodologymentioning
confidence: 99%
“…The maintenance of heavy metals like mercury and arsenic in aquatic environments could help bacteria in acquisition of metal resistance determinants located on the chromosome or plasmids [22]. Reports from the United States, the Netherlands, India, and Australia suggested the occurrence of heavy metal resistance among bacterial isolates [23][24][25][26]. Different resistance determinants are responsible for conferring resistance to heavy metals, e.g., mer and ars operon genes are responsible for resistance against mercury and arsenic, respectively [27].…”
Section: Introductionmentioning
confidence: 99%